2014
DOI: 10.9790/0853-131261821
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Pattern of Bacterial Isolates from Catheterised Patients in a Referral Hospital

Abstract: Introduction: Catheter associated urinary tract infection is one of the most important Result: A total of 11 samples were positive and 12 organisms were isolated, of which 3 were Gram positive and 9 were Gram negative organisms. The most common Gram positive isolate was S.aureus and E.coli was the most common Gram negative isolate. All the S.aureus isolates were Methicillin resistant (MRSA). But it was 100% sensitivity to vancomycin, linezolid and co-trimoxazole. As for the gram negative organisms, it was most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In the present study Escherichia coli was isolated in 27.2 % of CAUTI cases. Similar results have been reported in studies performed by Chaudhari et al, 21 , and Roel et al, 27 , with rate of isolation to be 21% and 27.2% respectively. However Poudel et al, 22 have reported a higher isolation rate of E. coli (40.7%).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study Escherichia coli was isolated in 27.2 % of CAUTI cases. Similar results have been reported in studies performed by Chaudhari et al, 21 , and Roel et al, 27 , with rate of isolation to be 21% and 27.2% respectively. However Poudel et al, 22 have reported a higher isolation rate of E. coli (40.7%).…”
Section: Resultssupporting
confidence: 91%
“…However studies conducted by Chatterjee et al, 23 and Dimri et al, 24 reported a higher rate of CAUTI (86.6% and 86.1% respectively). A lower rate of CAUTI has been reported by Bhatia et al, 25 (28.8%), Prajapati et al, 26 (13.14%) and Roel et al, 27 (15.5%).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The increasing number of CAUTIs bears on the fact that urinary catheters became second most often used foreign body inserted into human body [ 15 ]. Several other studies [ 16 , 17 ] have shown P. aeruginosa is the second most common gram negative microorganism isolated from catheterized patient with UTI. The prevalence of P. aeruginosa in the current study was found to be 49.…”
Section: Discussionmentioning
confidence: 99%
“…The isolate were susceptible to Ciprofloxacin and Norfloxacin. The Susceptibility of the isolates to Ciprofloxacin is very important for local consumption compared to other studies, whereby 40.5 % [ 24 ], 50 % [ 17 ] and 72.41 % [ 25 ] susceptibility were observed, Ciprofloxacin should be given due attention and should be used when necessary as an alternative therapeutic agent for resistant isolates.…”
Section: Discussionmentioning
confidence: 99%